Etiology of size based pulmonary nodules in Asia. - Saenghirunvattana, Sawang; Kurimoto, Noriaki; Suwanakijboriharn, Chokchai; Napairee, Chittisak; Pitiguagool, Vitoon; Saenghirunvattana, Chao; Gonzales, Maria Christina; Sutthisri, Kritsana; Siangproh, Chitchamai (The Bangkok Medical Journal, 2016)
OBJECTIVE: To determine whether the American College of Chest Physicians’ lungnodule screening recommendation is an effective tool in diagnosing Asian patientswith pulmonary nodules. MATERIALS AND METHODS: This is a retrospective study of 36 patients from2012-2014 that were identified to have had pulmonary nodules through chest CT scanresults. The data collected from patients were evaluated then illustrated to find out thenature of lung nodules among Asian population. The pulmonary nodule is based onsize alone regardless of other morphology for instance border, calcification etc.RESULTS: Out of 36 patients, 23 were diagnosed with tuberculosis (TB), 19 testedpositive for lung malignancy, 5 cases of TB co existing with cancer and 6 cases ofnon-tuberculous mycobacterium (NTM) infection. The types of lung cancer foundwere 7% small cell lung cancer, 7% squamous cell lung cancer and 86% adenocarcinoma.Nodule sizes were classified into 3 groups according to measurement. 4.5-11 mm (100%TB and 0% cancer), 12-20 mm (60% TB and 40% cancer) and 21-88 mm (52% TBand 48% cancer). CONCLUSION: Lung nodule evaluation among Asian patients requires specific guidelinesthat consider the high prevalence of tuberculosis and other infections. The statisticalresults from our study proves that the American College of Chest Physicians’ lung nodulescreening recommendation, if practiced by Asian physicians, should be revised accordingto the current health status and presence of other diseases of the Asian population.